2020
DOI: 10.1007/s00266-020-01710-5
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Obstruction and Rhinoplasty: A Focused Literature Review

Abstract: Background There is a significant variation in the assessment, treatment, and outcomes of nasal airway obstruction and management in the published literature. This study aimed to: (1) define key components of the nasal airway, (2) identify frequent causes of nasal obstruction, and (3) review existing treatment methods. Methods A systematic review of the literature was performed, and 135 studies were included via the following criteria: English, human subjects, and a primary endpoint of nasal airway improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 133 publications
0
10
0
2
Order By: Relevance
“…Independently of the AR diagnosis, previous studies with different objective and subjective methods have demonstrated that a general improvement in nasal obstruction is achieved after STP. 8,9,11,[18][19][20] The results regarding determination of AR as a predictive factor for less improvement in STP have been contradictory in recent studies. Mondina et al studied 100 patients after STP, among whom 28 presented AR, using the NOSE and RhinoQoL questionnaires before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Independently of the AR diagnosis, previous studies with different objective and subjective methods have demonstrated that a general improvement in nasal obstruction is achieved after STP. 8,9,11,[18][19][20] The results regarding determination of AR as a predictive factor for less improvement in STP have been contradictory in recent studies. Mondina et al studied 100 patients after STP, among whom 28 presented AR, using the NOSE and RhinoQoL questionnaires before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Independently of the AR diagnosis, previous studies with different objective and subjective methods have demonstrated that a general improvement in nasal obstruction is achieved after STP. 8 , 9 , 11 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…NSD is the most common structural anomalies of the nasal cavity [5][6][7][8]. Nevertheless, the change of the sinonasal structure, which includes the MT, IT, nasal septum, anterior ethmoidal complex, uncinate process and nasal septal body, are also very common [12][13][14][15][16][17][18][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Se deberá llevar a cabo un examen físico del paciente, principalmente del sistema respiratorio superior: oídos, nariz y garganta. (22) La exploración física se acompañará de un minucioso estudio de su historia clínica o Anamnesis, que incluirá una serie de preguntas, como son: (22) • ¿Cuándo y cómo comenzó la congestión nasal?…”
Section: Pruebas De Diagnósticounclassified
“…Es frecuente observar en estos pacientes la escoliosis y el pie plano. (15,22) Las características físicas comunes de estos pacientes se conocen como síndrome del respirador bucal o de disfunción respiratoria, y sus características típicas son: (25) 1. Fascie típica con expresión de angustia (ojeras, ojos caídos, ojos enrojecidos, cara alargada, surco geniano y nasolabial marcados).…”
Section: Características Clínicasunclassified